2021
DOI: 10.1007/s12553-020-00492-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implementing a behavioral economics mobile health platform for individuals with behavioral health conditions

Abstract: Coordinated Behavioral Care’s (CBC) Pathway Home™ (PH) program partnered with Wellth, Inc., a mobile health platform grounded in behavioral economics theory, to help individuals with behavioral health conditions build and reinforce health habits by providing daily reminders to take medication, requiring tasks (photos demonstrating remembrance), and providing financial incentives tied to behaviors. CBC made Wellth, Inc. available to individuals enrolling in its PH program for the purpose of demonstrating the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There is significant research showing that contingency management improves treatment outcomes in the context of health concerns like substance use, medication and treatment adherence, and a range of health risk behaviors [70][71][72]. Some recent studies have shown that these types of incentives also increase digital intervention adherence for health behaviors [73,74]. Applications of contingency management specific to engagement with DMHIs are limited, but early results are promising.…”
Section: Intervention-level Engagement Considerationsmentioning
confidence: 99%
“…There is significant research showing that contingency management improves treatment outcomes in the context of health concerns like substance use, medication and treatment adherence, and a range of health risk behaviors [70][71][72]. Some recent studies have shown that these types of incentives also increase digital intervention adherence for health behaviors [73,74]. Applications of contingency management specific to engagement with DMHIs are limited, but early results are promising.…”
Section: Intervention-level Engagement Considerationsmentioning
confidence: 99%
“…Of the 53 enrolled users, 54.72% completed the full 90-day program and 66% completed over 70% of the possible task check-ins via the app. Two-thirds of participants indicated MI increased their tendency to take their medication and adhere to their care plan ( Granek et al, 2021 ). Similarly, in a naturalistic study of a 12-week digital fitness program, users who received MI for completing the program via their health plan were more than 12× more likely to complete the program than those who received no incentives ( Wurst et al, 2020 ).…”
Section: Monetary Incentives In Digital Interventions: Some Preliminary Evidencementioning
confidence: 99%
“…Of 125,369 health maintenance reminders sent for Medicare wellness visits, 77% (96,839) were nudge health maintenance reminders (ie, using behavioral economics-based language). Of 125,369 Medicare wellness visits health maintenance reminder portal messages sent, 60.2% (75,407) led to an appointment being scheduled, with 12.2% (15,342)…”
Section: Sample Characteristicsmentioning
confidence: 99%